Metabolome-Wide, Phylogenetically Controlled Comparison Indicates Higher Phenolic Diversity in Tropical Tree Species - Peguero, Guille; Gargallo-Garriga, Albert; Maspons, Joan; Klem, Karel; Urban, Otmar; Sardans, Jordi; Peñuelas, Josep (Plants (Basel, Switzerland), 2021)
Tropical plants are expected to have a higher variety of defensive traits, such as a more diverse array of secondary metabolic compounds in response to greater pressures of antagonistic interactions, than their temperate counterparts. We test this hypothesis using advanced metabolomics linked to a novel stoichiometric compound classification to analyze the complete foliar metabolomes of four tropical and four temperate tree species, which were selected so that each subset contained the same amount of phylogenetic diversity and evenness. We then built Bayesian phylogenetic multilevel models to test for tropical-temperate differences in metabolite diversity for the entire metabolome and for four major families of secondary compounds. We found strong evidence supporting that the leaves of tropical tree species have a higher phenolic diversity. The functionally closer group of polyphenolics also showed moderate evidence of higher diversity in tropical species, but there were no differences either for the entire metabolome or for the other major families of compounds analyzed. This supports the interpretation that this tropical-temperate contrast must be related to the functional role of phenolics and polyphenolics.
Keywords: antagonistic interactions; phenolics; metabolomics; plant defense; bayesian phylogenetic models; latitudinal biodiversity gradient